Kebijakan Pengelolaan Guru Madrasah Aliyah (Studi Kasus Kebijakan Pendidikan di MAN 1 Medan) - Ahmad Mukhlasin; Eka Lestari; Aprillia Nurul Azmi Batu Bara; Ihsan Saraini (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The teacher management policy in madrasah aliyah is a policy process using educational facilities and infrastructure as well as various strategies to achieve teacher management goals, namely realizing the position of teachers as professionals, as part of achieving the goals of implementing the national education system. This research aims to describe teacher management policies at MAN 1 Medan. This type of research uses qualitative descriptive research with observation, documentation and interview techniques. The results of this research are that the teacher management policy at MAN 1 Medan is considered good, this can be proven by the results of the speaker's research with WKM in the field of Curriculum. Where the teachers at MAN 1 Medan have carried out training to increase the competency of the teachers who teach at MAN 1 Medan. Apart from that, many teachers at MAN 1 Medan also have academic qualification certification.